An Interview Study with English Course Teachers On Teaching Writing Skills Through Google Meets During The Covid-19 Pandemic - Bradhiansyah Tri Suryanto; Achmad Syarif Hidayatullah (International Journal of English Education and Linguistics (IJoEEL), 2022)
During the COVID-19 pandemic, this study sought to investigate teachers' ability to integrate writing skills with online learning via Google Meetings. This was qualitative research with semi-structured interviews with a teacher at Zain Academy. Respondents were taken purposefully, namely teachers at Zain Academy who taught writing with Google Meet during the COVID-19 pandemic. This study will explicitly investigate (a) the availability of access to technology at the teacher's home and (b) the difficulties in teaching writing skills online through Google Meeting. The provisional finding of this study was that the availability of access to technology is very limited, and because of the instability of internet access, there are difficulties in maximizing online learning, especially in learning writing skills, because students are unable to open online classes due to frequent power outages or parallel WiFi interference, as well as the capacity and speed of internet access, which are not sufficient. The results of the interview informed the availability of access to technology and the difficulties in teaching writing skills online through Google Meetings during the COVID-19 pandemic. Based on the results of this research, it is hoped that it will provide insight into the impact of forced changes in teaching, which can have implications for teacher competence in terms of digitization, especially in teaching writing skills, which are very important skills for those who want to master written language in English properly and correctly.